Zwitterion‐Driven Shape Program of Prodrug Nanoassemblies with High Stability, High Tumor Accumulation, and High Antitumor Activity. Issue 23 (8th October 2021) - Li, Guanting; Sun, Bingjun; Zheng, Shunzhe; Xu, Lu; Tao, Wenhui; Zhao, Dongyang; Yu, Jiang; Fu, Shuwen; Zhang, Xuanbo; Zhang, Haotian; Zhai, Yinglei; Luo, Cong; et al.
Abstract: Prodrug nanoassemblies have emerged as a promising platform for the delivery of anticancer drugs. PEGylation is a "gold standard" to improve colloidal stability and pharmacokinetics of nanomedicines. However, the clinical application of PEG materials is challenged by in vivo oxidative degradation and immunogenicity. Rational design of advanced biomaterials for the surface modification of nanomedicines is the hot spot of research. Here, a zwitterionic sulfobetaine surfactant is constructed as a novel surface modifier to coassemble with 10‐hydroxycamptothecin‐linoleic acid conjugate, with the classical PEGylated material as control. Interestingly, both the type and ratio of surfactants have profound impacts on the molecular mechanisms of the assembly of prodrugs, thereby affecting the pharmaceutical properties. Compared with PEGylated spherical prodrug nanoassemblies, zwitterion‐modified prodrug nanoassemblies have distinct rod shape and superhydrophilic surface, and exhibit potent antitumor activity due to the combination of multiple advantages in terms of colloidal stability, cellular uptake, and pharmacokinetics. The findings illustrate the crucial role of zwitterionic surfactants as the surface modifier in the determination of in vivo fate of the prodrug nanoassemblies, and pave the way for the development of advanced nanomedicines. Abstract : Zwitterionic surfactant changes the morphology of prodrug nanoassemblies from nanospheres to distinct nanorods. Zwitterion‐modified prodrug nanoassemblies exhibit potent antitumor activity due to the combination of multiple advantages in terms of colloidal stability, cellular uptake, and pharmacokinetics. The findings illustrate the crucial role of zwitterionic surfactants as the surface modifier and pave the way for the development of advanced nanomedicines.